Kedudukan Hukum dan Kewenangan Pelaksana Tugas Direktur Utama Perumda Air Minum Kota Makassar - Muzakkir, Abd. Kahar; Husen, La Ode (Al-Ishlah: Jurnal Ilmiah Hukum, 2024)
The appointment of an Interim Director in the Regional-Owned Enterprise (ROE), notably a Regional Public Corporation for Water Utility in a crisis, often gives rise to juridical discourse concerning the scope of his or her authority, especially in making strategic policy decisions such as personnel restructuring. This normative legal research aims to analyze the validity of the appointment of the Interim President Director of the Regional Public Corporation for Water Utility of Makassar City, determine the legal regime governing the authority vested in this position, and assess the legality of the implemented personnel restructuring policy. Employing statute and conceptual approaches, this research examines various regulations related to ROEs, manpower law, and state administrative law. The analysis results indicate that the appointment of the Interim President Director by the Mayor of Makassar as the Capital Owner’s Authorized Representative amidst a total vacuum in the company’s organs has a strong juridical foundation. Furthermore, the authority of an Interim Director of the ROE is predominantly subject to the corporate law regime and sectoral ROE regulations, not to state civil service administrative norms, thereby granting authority equivalent to that of a definitive board of directors as stipulated in relevant regional regulations. Consequently, personnel restructuring policies, including non-renewal of employment contracts and termination of employment relations based on evaluations and company efficiency, are lawful and fall within the scope of the Interim President Director’s authority, provided they are implemented by applicable manpower law procedures and ROE regulations. This research provides juridical clarification to foster a more comprehensive legal understanding of the authority of an Interim Director of the ROE.